AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DAERAH - Annie Mustika Putri (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2019)
This research aims to examine wether there is an influence between organizational commitment, organizational culture, training and leadership style on the performance accountability of local government agencies. The data in this study are primary data obtained from questionnaires distributed directly to respondents. The data analysis model used is multiple linear regression. The results of the research organizational commitment influences the performance accountability, organizational culture influences the performance accountability, training influences the performance accountability, and leadership style influences the performance accountability.